PROFITABILITY ANALYSIS OF PT. BANK SYARIAH INDONESIA BEFORE AND AFTER THE MERGER - Rimayanti - Rimayanti; Dwita Sapitri (Tasharruf: Journal Economics and Business of Islam, 2023)
The breakthrough regarding the government’s policy to merge the three Islamic banks is expected to provide another choice of new financial institutions for the public and boost the national economy. This study aims to analyze the profitability before and after the merger of a bank, namely Bank Syariah Indonesia, resulting from the three state-owned banks: Bank Syariah Mandiri, Bank Rakyat Indonesia Syariah, and Bank Negara Indonesia Syariah. The type of research used was descriptive quantitative, so the authors conducted research using a comparative descriptive method by analyzing profitability ratios (ROA, ROE, ROI, OPM, and NPM). Data were obtained from financial reports published by Bank Syariah Indonesia. The results of this study on the average profitability value at Bank Syariah Indonesia stated that the ROA after the merger was higher than ROA before the merger, which was 1.19%; ROE after the merger was also much higher than before the merger, with a percentage of 11.87. The NPM and OPM ratios experienced a significant increase from conditions before the merger. The NPM ratio experienced a jump to 48.96%, while the OPM ratio increased almost three times to 44.54%. Meanwhile, the ROI value still shows a lower percentage than before the merger.